Comprehensive Quality Evaluation of Thick-Skinned Muskmelons Based on Nutritional Composition and Aroma Analysis - LI Chao, CHEN Wei, ZHENG Heyun, YANG Ying, YANG Mi, GENG Xinli, YANG Jun, SUN Yuping (Shipin Kexue)
In order to investigate the variations in nutritional and volatile compositions among different aroma types of thick-skinned muskmelons. Five new varieties (lines) of muskmelons with the potential for market promotion were selected for comparative analysis and comprehensive evaluation of their quality. The results revealed that orange-fleshed melons had significantly higher carotenoid content than did other colored-fleshed melons, while green-fleshed melons exhibit notably higher chlorophyll levels. s-3 (green-white fleshed) had significantly elevated levels of sucrose, total sugar, soluble solids, vitamin C, and sweetness relative to the other varieties (lines). A total of 1 241 volatile compounds were identified across all five muskmelon samples, the dominant ones being esters (20.23%), terpenoids (17.24%), ketones (11.85%), alcohols (9.43%), aldehydes (6.69%), and heterocyclic compounds. Notably, 27 esters, 26 aldehydes, 21 ketones, 21 terpenoids, 11 alcohols, 11 heterocycles, and 9 phenols with relative odor activity values (ROAV ≥ 1) were found to be shared among all varieties (lines). The esters and aldehydes in the flesh of s-4 (green fleshed), with higher diversity and greater ROAV than the other varieties (lines), contributed significantly to its aroma, being strong with a “Xieke melon-like” flavor. s-4 was a typical respiratory climacteric fruit. In summary, the variation in flavor profiles among these muskmelons was attributed to the differences in the composition and proportion of volatile constituents. The findings of this study provide a basis for enhancing the flavor and aroma of thick-skinned muskmelons and for establishing a comprehensive quality assessment framework for this fruit.